Hemoglobin Levels in Pregnant Women: A Cross-Sectional Study at Puskesmas Purwokerto Timur II, Indonesia - ROHMAH, JAZILATUR; WARDANI, DITA PRATIWI KUSUMA; AMBARWATI, DEWI; SUDARSONO, TANTRI ANALISAWATI (UNUSA Press, 2025)
Introduction: Hemoglobin is a crucial protein in red blood cells responsible for transporting oxygen and carbon dioxide throughout the body. According to the World Health Organization (WHO), an estimated 41.8% of pregnant women worldwide experienced iron deficiency anemia in 2012. In Indonesia, the prevalence of anemia among pregnant women remains high at 37.1%, with Banyumas District reporting an even higher rate of 50.7% in 2016. Objective: This study aimed to assess hemoglobin levels in pregnant women attending the Puskesmas Purwokerto Timur II, Banyumas District. Methods: A descriptive observational study with a cross-sectional design was conducted from April to May 2021. Data collection included respondent identity and medical history through questionnaires, while hemoglobin (Hb) levels were measured using the Azidemet method with the POCT (Point of Care Testing) device. A purposive sampling technique was employed, enrolling 20 respondents. Results: The results showed that 95% (19 out of 20) of the participants had normal hemoglobin levels. The mean Hb levels were 13.929 ± 0.6047 mg/dL in the first trimester, 11.500 ± 1.7804 mg/dL in the second trimester, and 13.067 ± 0.8501 mg/dL in the third trimester. Conclusions: Overall, none of the pregnant women included in the study were diagnosed with anemia.